Yard, street, park the design of suburban open space - Girling, Cynthia L.; Helphand, Kenneth I. (Wiley, 1994)
Yard Street Park was designed to help suburban community designers and planners deliver on the traditional promise of the best of both worlds. The authors take a hard look at more than a century of suburban planning and reconsider aspects of most developer-designed suburbs. They offer design alternatives based on open space planning methods that can be applied to new or existing developments to transform them into sustainable, livable communities